Mannosylation of pH-sensitive liposomes promoted cytoplasmic delivery of protein to macrophages: green fluorescent protein (GFP) performed as an endosomal escape tracer. (21st October 2021) - Yang, Kaiyun; Tang, Mingtan; Chang, Hao-Han; Kanamala, Manju; Davidson, Alan James; Wu, Zimei
Abstract: Conventional non-pH-sensitive liposomes for cytoplasmic delivery of protein suffer from poor efficiency. Here we investigated mannosylated pH-sensitive liposomes (MAN-PSL) for cytoplasmic delivery of protein to macrophages RAW 264.7 using PSL and non-pH-sensitive liposomes for comparison. We characterised the pH-dependent fluorescence of green fluorescent protein (GFP) and encapsulated it in liposomes as an intracellular trafficking tracer. GFP showed a reversed 'S'-shaped pH-fluorescence curve with a dramatic signal loss at acidic pH. GFP stored at 4 °C with light protection showed a half-life of 10 days (pH 5–8). The entrapment efficiency of GFP was dominated by the volume ratio of intraliposomal core to external medium for thin-film hydration. Mannosylation did not affect the pH-responsiveness of PSL. Confocal microscopy elucidated that mannosylation promoted the cellular uptake of PSL. For both these liposomes, the strongest, homogeneously distributed GFP fluorescence in the cytoplasm was found at 3 h, confirming efficient endosomal escape of GFP. Conversely, internalisation of non-pH-sensitive liposomes was slow (peaked at 12 h) and both Nile Red and GFP signals remained weak and punctuated in the cytosol. In conclusion, GFP performed as a probe for endosome escape of liposomal cargo. Mannosylation facilitated the internalisation of PSL without compromising their endosomal escape ability. Graphical abstract: UF0001